Perubahan Sikap Perempuan terhadapMasalah Menstruasi - Balango, Merry (Jurnal Pelangi Ilmu, 2008)
The essoy is a short note on women\'s culwal system and on the subject of women\'s attitude towatd menstruation. Menstruation is a universal phenomenon, yet one that in different culures takes on different meaning. The ruies of each nation, religion and belief to the mmstruating wome presents myhs and taboo.Women are likely to feel happy, loving, tmhappy, healthy, depressed, and sick- In another context, menstruating women mood shows the interactive effed of cdtwal, biological and religius events. Menstruation problems are described tltrough culare, religion, medical, patriarchal aspect. The opinion that\'women\'s attitude towmds menstruation influenced by sosial and cultural condilion are changeable, where biological and religious condition are not.